Biomechanical and physiological determinants of skiing locomotion development - Formenti, F.; Ardigo, L. P.; Minetti, A. E. (ISB Congress, 2005)
The present study will help historians to understand the times needed and distances covered during migrations in cold regions in the past. The research shows that the performances of two legendary historical journeys (1206 and 1520 AD) on snow, the performances of races originating from them (Birkebeiner and Vasaloppet) and those of other modern competitions (skating vs. classical techniques) are well predicted by the evolution of skiing economy.